2021
DOI: 10.1108/apjba-02-2021-0049
|View full text |Cite
|
Sign up to set email alerts
|

Why do micro-businesses hesitate to “grow up”?

Abstract: PurposeThis study analyzes the factors that affect the decisions of micro-businesses to switch to enterprises in Thanh Hoa, Vietnam.Design/methodology/approachIn order to explain the behavior of micro-businesses in switching to enterprises, the authors designed a questionnaire and collected survey data from 404 micro-businesses. The generalized structural equation modeling was applied to analyze the structured model with the dichotomous dependent variable.FindingsFirst, the behavior of micro-businesses to swit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
3
7
0
Order By: Relevance
“…Furthermore, this research demonstrated that even when a filter is applied to the CIIs, there are certain challenges, such as reluctance to give or receive responsibility, that needs to be overcome in micro-enterprises. Some of these challenges were also mentioned in the previous work (Hieu et al, 2021;Klute-Wenig and Refflinghaus, 2020;Inan and Bititci, 2015;Roy and Wheeler, 2006;Deichmann et al, 2004). Common problems experienced by micro-enterprises which were previously highlighted in the literature as low productivity, lack of financial assets, old manufacturing technologies and low-skilled employees (R€ ais€ anen and Tuovinen, 2020; Razak et al, 2018;Achtenhagen, 2017;Inan and Bititci, 2015) were also confirmed in this study.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, this research demonstrated that even when a filter is applied to the CIIs, there are certain challenges, such as reluctance to give or receive responsibility, that needs to be overcome in micro-enterprises. Some of these challenges were also mentioned in the previous work (Hieu et al, 2021;Klute-Wenig and Refflinghaus, 2020;Inan and Bititci, 2015;Roy and Wheeler, 2006;Deichmann et al, 2004). Common problems experienced by micro-enterprises which were previously highlighted in the literature as low productivity, lack of financial assets, old manufacturing technologies and low-skilled employees (R€ ais€ anen and Tuovinen, 2020; Razak et al, 2018;Achtenhagen, 2017;Inan and Bititci, 2015) were also confirmed in this study.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, following Hieu et al . (2021) and Katebi et al . (2022), we apply generalized SEM (GSEM), which is a combination of the generalized linear model and SEM (Zhang and Zhang, 2018).…”
Section: Methodsmentioning
confidence: 96%
“…The strength of this model is its powerful flexibility to jointly test a variety of hypotheses that involve different types of complicated cause–effect relationships (Katebi et al , 2022). However, the SEM's assumption (all responses are continuous) exposes users to severe biases, especially if the dependent variable is a dummy variable (Hieu et al , 2021). Therefore, following Hieu et al .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations